Effect of nanofluid-based absorbers on direct solar collector / Tham Chi Meng - Tham, Chi Meng (2011)
As conventional energy like fossil fuels is getting rare, cost of energy production has been increasingly higher. The concern of environmental pollution caused by burning of hydrocarbon fuels has also been raised among developed and developing nations. These make clean renewable energy a major research topic in recent decades. Among them, solar energy, as the most vastly available energy and also supremely effective in terms of energy conversion has been the most sought after. The most common solar thermal collector utilizes black surface as radiant absorber but the efficiency is limited to the effectiveness of the black surface and the transfer of thermal energy from the black surface to the working fluid. Direct Solar Collector, has come to be an innovative measure to this is by using nanofluids as volumetric absorber. Nanofluids are expected to provide excellent optical properties and enhanced thermal transfer. The aim of this study is to analyze the effect of nanofluid as working fluid for Direct Solar Collector. With aluminium nanoparticles as additive material and pure water as base fluid, the extinction coefficient of nanofluid is evaluated with nanoparticle size and volume fraction as parameters. The particle sizes and volume fraction studied are 1 nm to 10 nm and 0.1% to 8.0% respectively. The particle size shows minimal influence to the optical properties of nanofluid while the extinction coefficient is linearly proportionate to volume fraction. The transmissivity of light is compared between pure water (base fluid) and nanofluid. The improvement is promising and with only 1.0% volume fraction, the nanofluid is already almost opaque to light wave.